Cangrelor: a review on pharmacology and clinical trial development. (October 2013) - Franchi, Francesco; Rollini, Fabiana; Muñiz-Lozano, Ana; Rae Cho, Jung; Angiolillo, Dominick J
Dual antiplatelet therapy with aspirin and an oral ADP P2Y12 receptor antagonist is the standard-of-care for the prevention of ischemic events in patients with acute coronary syndrome or undergoing percutaneous coronary intervention (PCI). However, currently available ADP P2Y12 receptor antagonists have several limitations, such as interindividual response variability, drug–drug interactions, slow onset/offset and only oral availability. Cangrelor is a reversible, potent, intravenous, competitive inhibitor of the ADP P2Y12 receptor that rapidly achieves near complete and predictable platelet inhibition. Along with reversible binding to the receptor cangrelor also has a very short half-life (3–5 min), which in turn results in a rapid offset of action. These properties make cangrelor a promising drug for clinical use in patients undergoing PCI or patients waiting for major surgery but still require antiplatelet protection. This manuscript provides an update of the current status of knowledge on cangrelor, focusing on its pharmacologic properties and clinical trial development, including the BRIDGE and CHAMPION-PHOENIX trials.